Domino Transformations of Ene/Yne Tethered Salicylaldehyde Derivatives: Pluripotent Platforms for the Construction of High sp3 Content and Privileged Architectures. Issue 69 (20th September 2019) - Sebastian, Anusha; Srinivasulu, Vunnam; Abu‐Yousef, Imad A.; Gorka, Orive; Al‐Tel, Taleb H.
Abstract: Diversity‐oriented synthesis (DOS) has become a powerful synthetic tool that facilitates the construction of nature‐inspired and privileged chemical space, particularly for sp 3 ‐rich non‐flat scaffolds, which are needed for phenotypic screening campaigns. These diverse compound collections led to the discovery of novel chemotypes that can modulate the protein function in underrepresented biological space. In this context, starting material‐driven DOS is one of the most important tools used to build diverse compound libraries with rich stereochemical and scaffold diversity. To this end, ene/yne tethered salicylaldehyde derivatives have emerged as a pluripotent chemical platform, the products of which led to the construction of a privileged chemical space with significant biological activities. In this review, various domino transformations employing o ‐alkene/alkyne tethered aryl aldehyde/ketone platforms are described and discussed, with emphasis on the period from 2011 to date. Abstract : Building diversity : Starting material‐driven diversity‐oriented synthesis (DOS) is one of the most important tools used to build diverse compound libraries with rich stereochemical and scaffold diversity, particularly for nature‐inspired sp 3 ‐rich non‐flat scaffolds. To this end, ene/yne tethered salicylaldehyde derivatives have emerged as a pluripotent chemical platform, the products of which led to the construction of a privileged chemical space with significant biological activities.